Correction: Spatial Distribution Patterns in the Very Rare and Species-Rich Picea chihuahuana Tree Community (Mexico) - Wehenkel, Christian; Brazão-Protázio, João Marcelo; Carrillo-Parra, Artemio; Martínez-Guerrero, José Hugo; Crecente-Campo, Felipe (PloS one, 2015)
[This corrects the article DOI: 10.1371/journal.pone.0140442.].